PENTINGNYA KELUARGA UNTUK PEMBENTUKAN MORAL ANAK BINAAN DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS I KUTOARJO - Saputro, Setyo Aji; Rifani, Denny Nazaria (Universitas Nusa Cendana, 2024)
Crime is an individual behavior that violates the rules and is followed up with sanctions in the form of criminal law. Children who commit crimes are considered victims who need protection, guidance, and rehabilitation following human rights and the characteristics and needs of children. Therefore, the juvenile criminal justice system must pay attention to children's rights, principles of justice, and a balance between community protection, victims' rights, and children's interests (Law number 22 of 2022). These correctional students are placed in special prisons that accommodate children who commit crimes, namely the Children's Correctional Institution (LPA) or the Children's Detention Center (Rutan). Keywords: Family Role; Moral Formation; Child Morals